2011
DOI: 10.4321/s1695-61412011000300008
|View full text |Cite
|
Sign up to set email alerts
|

La evaluación en la enseñanza de grado en enfermería en América Latina: una revisión integrativa

Abstract: La evaluación en la enseñanza de grado en enfermería en América Latina: una revisión integrativaAvaliação no ensino de graduação em enfermagem na America Latina: uma revisão integrativa *Vasconcelos, CM da CB., **Backes, VMS., ***Gue, JM.*Enfermeira e Coordenadora Local de Saúde da Secretaria Municipal de Florianópolis-Santa Catarina. Membro do Grupo de Pesquisa em Educação em RESUMENArtículo de revisión integrativa de la literatura sobre las tendencias o modelos de evaluación en la enseñanza de grado en enfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 4 publications
0
4
0
2
Order By: Relevance
“…In order to make it work in practice, clear assessment criteria must be established, in line with principles that will serve as a basis for judgment. In other words, principles that foster integration among the stakeholders involved in the assessment process [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to make it work in practice, clear assessment criteria must be established, in line with principles that will serve as a basis for judgment. In other words, principles that foster integration among the stakeholders involved in the assessment process [21].…”
Section: Discussionmentioning
confidence: 99%
“…The PPP of higher education institutions will have to be based on a pedagogical approach that is transformative, emancipating, liberating and sympathetic, focusing on training professionals who are fully aware of their responsibilities and duties [21].…”
Section: Discussionmentioning
confidence: 99%
“…It is indicated that the evaluation should be a facilitating instrument for the individual's continuous growth, motivating and incorporating specific values and skills. 11 Questions regarding the topics covered were randomly distributed so that those involved, together with their peers, could answer considering the learning.…”
Section:  Faculty Experiencementioning
confidence: 99%
“…Se realizó una revisión integrativa que busca sintetizar el conocimiento con un enfoque sistemático y riguroso 7 . La revisión se realizó por etapas: en la primera se identificaron las escalas más utilizadas para medir calidad de vida en pacientes con ERCA, para ello se establecieron 3 ecuaciones de búsqueda utilizando palabras clave según los descriptores MeSH y DeCS (Quality of Life, Kidney Diseases, SCALE, Dialysis, kidney transplantation, Conservative Treatment) en las diferentes combi-naciones posibles con los operadores booleanos (AND, OR) en las bases de datos: CINAHL, CUIDEN, MED-LINE, NURSING OVID, y metabuscador BIBLIOTECA VIRTUAL DE SALUD.…”
Section: Materials Y Métodounclassified